VEGF-D Serum Level as a Potential Predictor of Lymph Node Metastasis and Prognosis in Vulvar Squamous Cell Carcinoma Patients - Ravaggi, Antonella; Gambino, Angela; Ferrari, Federico; Olivari, Alessandro; Zanotti, Laura; Romani, Chiara; Ardighieri, Laura; Antonelli, Paolo; Garganese, Giorgia; Gallo, Daniela; Scambia, Giovanni; Bignotti, Eliana; et al. (Frontiers in Oncology, 2022)
Background Radical surgical resection of the primary tumor with mono/bilateral inguinofemoral lymph node dissection is the standard treatment for invasive vulvar squamous cell carcinoma (VSCC) and is frequently related to severe morbidity. Tailoring surgical treatment is of paramount importance, and a comprehensive preoperative evaluation is mandatory. Vascular endothelial growth factor D (VEGF-D) is considered a regulator of lymphangiogenesis involved in tumor spread via lymphatic vessels. The aim of this study was to evaluate the potential of VEGF-D in the prediction of inguinofemoral lymph node metastasis. Methods We analyzed the preoperative levels of serum VEGF-D (sVEGF-D) from two independent cohorts of patients with VSCC by enzyme-linked immunosorbent assay and its protein expression on tumor tissue by immunohistochemistry. Logistic regression was performed to identify the independent risk factors for lymph node metastasis, and Cox proportional hazard model was used for survival analysis. Results High levels of sVEGF-D, but not tissue VEGF-D, significantly correlated with positive groin nodes and a more advanced International Federation of Gynecologists and Obstetricians (FIGO) stage. In multivariable analysis, a high sVEGF-D level was an independent predictor of lymph node metastasis and worse prognosis. A prediction model based on sVEGF-D, tumor grade assessed on biopsy, tumor diameter, and lymph node clinical evaluation was able to predict lymph node metastasis, reaching C-index values of 0.79 and 0.73 in the training and validation cohorts, respectively. Conclusions The preoperative sVEGF-D level might be a reliable biomarker for the prediction of lymph node metastasis and prognosis in patients with VSCC, supporting better clinical/surgical decision. Multicenter prospective studies are required to confirm our findings.